High-Dose Betahistine Improves Cognitive Function in Patients With Schizophrenia: A Randomized Double-Blind Placebo-Controlled Trial - Wang, Yongqian; Huang, Xufeng; Fan, Hongzhen; An, Huimei; Ma, Ting; Zhang, Qi; Zhao, Wenxuan; Yun, Yajun; Yang, Wenshuang; Zhang, Xiaolu; Wang, Zhiren; Yang, Fude (Frontiers in Psychiatry, 2021)
Abstract Background: There is currently no effective treatment for cognitive impairment associated with schizophrenia (CIAS). Recent studies have shown that increased histamine levels in the brain may help to improve CIAS symptoms. Betahistine is an H1-receptor agonist and H3-receptor antagonist. This study evaluated the effect of high-dose betahistine on cognitive function as well as its safety in Chinese Han patients with schizophrenia. Methods: This randomized double-blind, placebo-controlled trial enrolled 89 patients with schizophrenia who were randomly administered betahistine (72 mg/d) or placebo for 12 weeks. At baseline and at 4, 8, and 12 weeks after commencing the intervention, we measured changes in cognitive function and clinical symptoms using the MATRICS Consensus Cognitive Battery (MCCB) and Positive and Negative Syndrome Scale (PANSS), respectively. Furthermore, we used the Treatment Emergent Symptom Scale (TESS) to assess the adverse effects of the patients’ medications. Results: Compared to the placebo group, the betahistine group showed significant improvements in the MCCB composite score after 12 weeks of treatment (p=0.003) as well as improvements in MCCB verbal learning (p=0.02) and visual learning (p=0.001) domain scores. However, there were no significant improvements in the PANSS total scores or subscores (p>0.05). Generally, high-dose betahistine treatment was considered safe in patients with schizophrenia. Conclusions: Additional use of high-dose betahistine can effectively improve cognitive function but not psychiatric symptoms in patients with schizophrenia. Betahistine (72 mg/d) is well tolerated by Chinese Han patients with schizophrenia. Trial Registration: chictr.org.cn, ChiCTR1900021078 http://www.chictr.org.cn/edit.aspx?pid=35484&htm=4